Critical Analysis of Consumer Protection in “Lootbox” Virtual Transaction System in Indonesia - Dende Ratna Sari Marinah; Ardi Krisna Wardana; Baiq Vatriana Sasa Wisesa; Fradisti Reta Ikasari Mediana; Mas'adah Mas'adah (Faculty of Law, University of Mataram, 2020)
Purpose of this research is to determine consumer protection regulation for virtual (Lootbox) transactions in Indonesia. The research method is normative legal studies. Results of the study is that virtual transactions are easily carried out, such as loot box virtual transactions that is affected to financial loss for both consumers and countries. Regulations that have made by several countries need to be further analyzed and examined in order to be implemented and regulated as in the country of Belgium issuing rules that require the (Lootbox) to be banned or be subjected to sanctions for violations of the Gambling Law in that country. So that Indonesia should make (Lootbox) regulation even though the regulation is unspecified in KUHP and Bill of Act on Electronic Information and Transaction that can make consumers protection is more guaranteed.